Identifying Drug-Target Selectivity of Small-Molecule CRM1/XPO1 Inhibitors by CRISPR/Cas9 Genome Editing. Issue 1 (22nd January 2015) - Neggers, Jasper E.; Vercruysse, Thomas; Jacquemyn, Maarten; Vanstreels, Els; Baloglu, Erkan; Shacham, Sharon; Crochiere, Marsha; Landesman, Yosef; Daelemans, Dirk
Summary Validation of drug-target interaction is essential in drug discovery and development. The ultimate proof for drug-target validation requires the introduction of mutations that confer resistance in cells, an approach that is not straightforward in mammalian cells. Using CRISPR/Cas9 genome editing, we show that a homozygous genomic C528S mutation in the XPO1 gene confers cells with resistance to selinexor (KPT-330). Selinexor is an orally bioavailable inhibitor of exportin-1 (CRM1/XPO1) with potent anticancer activity and is currently under evaluation in human clinical trials. Mutant cells were resistant to the induction of cytotoxicity, apoptosis, cell cycle arrest, and inhibition of XPO1 function, including direct binding of the drug to XPO1. These results validate XPO1 as the prime target of selinexor in cells and identify the selectivity of this drug toward the cysteine 528 residue of XPO1. Our findings demonstrate that CRISPR/Cas9 genome editing enables drug-target validation and drug-target selectivity studies in cancer cells.